Benefits and costs of coporate debt restructuring : an estimation for Korea - Chung, Jae-Yong; Chung, Jae-Yong; Ratnovski, Lev (IMF working paper ;, 2016)
The paper offers a method to quantify benefits and costs of corporate debt restructuring, with an application to Korea. We suggest a "persistent ICR<1" criterion to capture firms that had ICR<1 for multiple consecutive years and thus will likely require restructuring. We assess the benefits of debt restructuring by estimating the effects of removing a firm's debt overhang on its investment and hiring decisions. We refine the assumptions on the cost of debt restructuring based on the literature, and focus not only on creditor losses, but also on the employment impact of corporate restructuring. Benchmark results for Korea suggest 5.5-7.5 percent of GDP creditor losses and a 0.4-0.9 percent of the labor force employment impact from the debt restructuring. These are compensated by a permanent 0.4-0.9 percentage points increase in future GDP growth thanks to higher corporate investment and 0.05-0.1 percent of labor force higher hiring in the subsequent years. The key qualitative result is that corporate debt restructurings "pay off" in the medium term: their economic cost is recouped over about 10 years